2006
DOI: 10.1002/eji.200635972
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4 induces expression of TARC/CCL17 via two STAT6 binding sites

Abstract: A cardinal feature of allergic disorders and immune responses is enhanced leukocyte trafficking. This is largely orchestrated by chemokines. The CC chemokine thymus-and activation-regulated chemokine (TARC/CCL17) selectively attracts Th2 cells via the G protein-coupled chemokine receptor CCR4. We show here that TARC/CCL17 is expressed by human T cells upon stimulation with IL-4. Mapping of the transcriptional start site revealed the presence of two putative STAT6 binding motifs in proximity to the start positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 52 publications
5
82
0
Order By: Relevance
“…1C) and increased goblet cell mucus production (assessed by periodic acid-Schiff staining; data not shown). Consistent with the ability of IL-13 to increase expression of chemokines that regulate eosinophil and lymphocyte chemotaxis (5,(37)(38)(39), the levels of mRNA encoding CCL11 (eotaxin-1), CCL17 (thymus and activation-regulated chemokine), and CCL22 (macrophage-derived chemokine) were also increased (Fig. 1C).…”
Section: Intranasal Delivery Of Ril-13 Induces Ahr Airway Inflammatisupporting
confidence: 72%
“…1C) and increased goblet cell mucus production (assessed by periodic acid-Schiff staining; data not shown). Consistent with the ability of IL-13 to increase expression of chemokines that regulate eosinophil and lymphocyte chemotaxis (5,(37)(38)(39), the levels of mRNA encoding CCL11 (eotaxin-1), CCL17 (thymus and activation-regulated chemokine), and CCL22 (macrophage-derived chemokine) were also increased (Fig. 1C).…”
Section: Intranasal Delivery Of Ril-13 Induces Ahr Airway Inflammatisupporting
confidence: 72%
“…Quantitative RT-PCR (qRT-PCR) was done as described previously (29). In brief, total RNA was isolated with TRIzol (Invitrogen, Lofer, Austria) or a Nucleospin RNA II kit (Macherey-Nagel, Düren, Germany), according to the manufacturer's instructions.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…TARC/CCL17, a ligand for CC chemokine receptor 4 and CC chemokine receptor 8, serves for the recruitment and migration of lymphocytes of the Th2 phenotype (8,9) and direct T-cell and macrophage recruitment into areas of allergic inflammation. In human and animal studies, it is demonstrated that TARC/CCL17 mRNA and protein are potently induced by the Th2 cytokine, interleukin-4 (IL-4), through induction of promoter binding of signal transducer and activator of transcription 6 (STAT6) (17,18). IL-4/signal transducer and activator of transcription 6 signaling during T-cell development contributes to polarized patterns of cytokine expression manifested by differentiated Th cells (19).…”
Section: Plasma Tarc/ccl17 Levels In the Different Genotypes Of Kd Pamentioning
confidence: 99%